ProtChemSI: a network of protein-chemical structural interactions - Kalinina, Olga V.; Wichmann, Oliver; Apic, Gordana; Russell, Robert B. (Nucleic acids research, 2012)
Abstract. Progress in structure determination methods means that the set of experimentally determined 3D structures of proteins in complex with small molecules